Alternatif Penanganan Losses Akibat Ketidakseimbangan Beban Pada Trafo Distribusi - Anang Dasa Novfowan; Mochammad Mieftah; Wijaya Kusuma (Politeknik Negeri Malang, 2023)
The unbalanced load on distribution transformers is mostly caused of connecting new customers and changing patterns of electricity usage in the community. The impact of the unbalanced load is the emergence of a current flowing on the transformer neutral conductor that causes energy losses. Load balancing of distribution transformers is commonly done by technicians, but the implementation takes quite a long time and is repeated, sometimes up to 4-5 times to get the appropriate results. This is more due to less valid customer phase data. Customer phase verification is needed to accelerate the load balancing process in an effort to reduce losses in distribution transformers. With valid customer phase data, just one stage of load balancing can reduce losses by 1.06%..